CROWN RUST RESISTANCE IN HYBRID AVENA (AVENA STERILIS AND AVENA SATIVA) - I. Hammami1; M. Elgazzah (Journal of Animal and Plant Sciences, 2020)
Oat production is usually menaced by the presence of overwhelming pathogens worldwide. Oat crown rust disease causes significant yield losses in cultivated oat. Characterization of the genetic components underlying disease resistance is highly relevant for resistance breeding programs. Interspecific crossing was made between the resistant ecotype, spontaneous oats (Avena sterilis) and a susceptible cultivated oat (Avena sativa). Resistance to crown rust was assessed using the area under the disease progress curve (AUDPC) for each individual plant. Parents were not only contrasting by their reaction to the phytopathogen, but also by their kernel morphology. In spontaneous oat flowers, the lemma is easily dislodged and showed single long twisted geniculate awn, whereas cultivated lines were having opposite characters. Kernel phenotype analysis among F2, F3 and BC1S1 plants showed that each awn development pattern could be encoded by one semi-dominant factor. Recessive homozygote genotype meant awnless, While, heterozygosis genotype showed an intermediate phenotype. Diversity in awn length and awn number in F2 and F3 kernels could be explained by all the possible recombination’s of the two factors. Analysis of resistant and susceptible ratio in F2 and F3 hybrids using Chi-squared (χ2) test showed that resistance to oat crown rust of JT0 seemed to be oligogenic and may be encoded by three dominant genes with epistatic effects. Whereas, JT5 resistance trait could be encoded by a single dominant gene. Combination of these genes in a local oat cultivar could be an efficient way to reduce losses caused by crown rust disease.
Keywords: Avena sterilis; Avena sativa; crown rust; Awn development; kernel